The Effect of Public Communication in Increasing the Effectiveness of Public Services: Case Study on Public Services in West Bandung District - Ayuna, Novianty Elizabeth; Zairusi, Zairusi; J. Pratama, Roro Arinda Reswanti; Eryanto Septiawan, Fajar; Gintings, Abdorrakhman (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to investigate the important role of public communication in increasing the effectiveness of public services with a locus in West Bandung Regency. As respondents, there were 153 people in the community who received various services from the district office during August 2023. The analysis focused on how effective public communication can influence positive results in providing services to the community. A quantitative approach was used in this research by collecting data through surveys and statistical analysis. The results of this research show that public communication has a positive and significant influence on public services. It is recommended that communication competency be one of the materials in training for new West Bandung Regency employees.